PENERAPAN MODEL PEMBELAJARAN PROJEK BASED LEARNING (PjBL) BERBASIS TPaCK - Rochmadi, Nur Wahyu; Rochastuti, Larasati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
the quality of human resources are increasing, not only must they be knowledgeable, skilled and have character, but they must also be productive (productive), suitable for publication and profitable. These conditions create a learning model that requires students to produce